Chemokine-Like Factor-Like MARVEL Transmembrane Domain-Containing Family in Hepatocellular Carcinoma: Latest Advances - Li, Mengxia; Luo, Fangzhou; Tian, Xinyao; Yin, Shengyong; Zhou, Lin; Zheng, Shusen (Frontiers in Oncology, 2020)
Chemokine-like factor (CKLF)-like MARVEL transmembrane domain-containing family (CMTMs) is a new gene family, consisting of CKLF and CMTM1 to CMTM8, which play an important role in hematopoiesis system, autoimmune diseases, male reproduction etc. Abnormal expression of CMTMs is also associated with tumor genesis, development and metastasis. In this review, we briefly describe the characteristics of CMTM family, outline its functions in multiple kinds of carcinomas, and summarize the latest research on their roles in hepatocellular carcinoma which are mainly related to the expression, prognostic effect, potential functions, and mechanism of action. The CMTM family is expected to provide new ideas and targets for HCC diagnosis and treatment.